Inserção de microgeração distribuída nas redes de baixa tensão: implantação de telhados solares - estudo de caso real - Marcio Eli Moreira de Souza (2014)
The new scenario of the Brazilian power generation sector, established by the national agency of electrical energy, considers a diverse portfolio of encouraged energy sources. This brought to distribution companies a different and complex outlook to expansion, operation and maintenance activities of their networks and assets. The insertion of these generation sources, considered as Distributed Generation, once they are connected directly to the distribution networks of low voltage or medium voltage, represents a major challenge. Distribution networks are designed to operate in a radial way, i.e., in single power flow direction and this new scenario will operate in ring with double direction of power flow. Thus, the goal of this dissertation is to discuss the impacts of the connection of distributed generation to low voltage distribution networks. Also, it indicates alternatives to mitigate these impacts, addressing in more detail a real case of connection of photovoltaic generation units at a low voltage circuit.